Facile fabrication of zeolitic imidazolate framework hollow fibre membranes via a novel scalable continuous fluid circulation process. Issue 35 (29th July 2021) - Lewis, Allana; Chen, Ting; Butt, Fraz Saeed; Wei, Xiuming; Radacsi, Norbert; Fan, Xianfeng; Huang, Yi
Abstract : A scalable continuous fluid circulation process is employed to fabricate ZIF hollow fibre membranes. Individual circulation of synthesis solutions resulted in a uniform seed layer, improving ZIF membrane growth and its liquid separation performance. Abstract : A novel continuous fluid circulation system was designed and employed for the impregnation seeding and fabrication of zeolitic imidazolate framework (ZIF) crystals on the internal surface of polymeric hollow fibre membranes. Application of impregnation seeding has been proven effective to decrease crystal size, consequently increasing surface roughness and wettability of the membrane. Evaluation of the as-synthesised membrane demonstrated excellent separation efficiencies (>99%) of surfactant stabilised oil-in-water emulsions. Owing to the simple impregnation strategy assisted by the continuous fluid circulation, the active ZIF layer formed was visibly thinner and denser than typical seeding techniques, hence a high pure water flux of >1150 L m −2 h −1 bar −1 was achieved. The membranes were highly selective and ultra-permeable to water, however, almost impermeable to oils in a water environment, e.g., n -hexane, n -heptane, chloroform and dichloromethane, as well as their emulsion mixtures, with a separation efficiency higher than 99%. Besides, this new continuous fluid circulation method was also found promising for the synthesis of other types of ZIF on hollow fibre membranes.